Financial distress, political affiliation and earnings management: the case of politically affiliated private firms. Issue 6 (13th April 2019) - Jacoby, Gady; Li, Jialong; Liu, Mingzhi
Abstract : Using a sample of politically affiliated private firms in China, we explore the relation between corporate financial distress and earnings management. We further examine the joint moderating effects of political affiliation and regional development on this relation. The findings suggest that financially distressed firms engage more in reporting small positive earnings relative to financially healthy firms. In addition, political affiliation weakens the association between financial distress and small positive earnings management. A three-way interaction analysis indicates that the moderating effect of political affiliation is influenced by regional development.